Preservice Science Teachers’ Instructional Design Competence: Characteristics and Correlations - Zhang, Ronghua; Liu, Xiufeng; Yang, Yang; Tripp, Jennifer; Shao, BoYu (Eurasia Journal of Mathematics, Science and Technology Education, 2018)
Underpinned by a holistic, dynamic, and process-oriented view of teacher competences, this study provides an analytic hierarchy system of instructional design competence (IDC) for evaluating teachers’ IDC based on the mental model of instructional design. Additionally, this study quantitatively explores the IDC characteristics and correlations of 118 preservice science teachers at Shanxi Normal University in China, who learned the ADTRE (analyzing, designing, teaching, revising, and evaluating/improving) instructional model, based on reflection and feedback. Using lesson planning (LP) scoring rubrics, we analyzed 113 lesson plans from 56 participants majoring in biological science and 57 in biological technology. We present the ADTRE model and discuss relationships between preservice science teachers’ academic achievement and IDC. Major findings include a positive correlation between preservice science teachers’ IDC scores and their course grades in Advanced Mathematics and Cell Biology and concept mapping skills. There was a negative correlation between preservice science teachers’ IDC and course grades in Principles of Genetic Engineering and Technology, and no significant correlations existed between IDC and course grades for teacher education courses. Our findings reveal the nature of preservice science teachers’ IDC, a potential for improvement in university teacher education curricula, and a need for further research.